Agglomeration processes in ageing societies - Theresa Grafeneder-Weissteiner; Klaus Prettner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2010)
This article investigates agglomeration processes in ageing societies by introducing an overlapping generation structure into a New Economic Geography model. Whether higher economic integration leads to spatial concentration of economic activity crucially hinges on the economies' demographic properties. While population aging as represented by declining birth rates strengthens agglomeration processes, declining mortality rates weaken them. This is due to the fact that we allow for nonconstant population size. In particular, we show that population growth acts as an important dispersion force that augments the distributional effects on agglomeration processes resulting from the turnover of generations.
Keywords: R12; J10; F15; C61; 330; Agglomeration; population aging; population; Agglomerationseffekt; Alternde Bevölkerung; Bevölkerungswachstum; Overlapping Generations; Neue ökonomische Geographie; Theorie